ESTIMATING THE YIN-YANG NATURE OF WESTERN HERBS: A POTENTIAL TOOL BASED ON ANTIOXIDATION- OXIDATION THEORY - Gilca, Marilena; Gaman, Laura; Lixandru, Daniela; Stoian, Irina (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background : One of the biggest obstacles to progress in traditional Chinese medicine (TCM) development in Western countries is the difficulty of applying the traditional concepts to the Western medicinal plants, which are not traditionally described in ancient literature. During recent years, new advances in the field of understanding Yin/Yang aspects from a modern bioscientific point of view have led to the conclusion that antioxidation-oxidation concepts might mirror a Yin-Yang relationship. Methods: This study was intended to integrate the Yin-Yang theory of the traditional Chinese medicine with modern antioxidation-oxidation theory, and to propose a biochemical tool based on redox parameters (e.g. antioxidant capacity, chemiluminescence-CL signal inducing capacity), usable for the classification of Western medicinal plants from Yin/Yang perspective. Trolox equivalent antioxidant capacity (TEAC) of six vegetal aqueous extracts (Symphitum officinalae (radix)- SYM, Inula helenium (radix)- INU, Calendula officinalis (flores)- CAL, Angelica arhanghelica (folium)- ANG(F), Angelica arhanghelica (radix)- ANG(R), Ecbalium Elaterium (fruits)- ECB) and luminol-enhanced chemiluminescence of PMNL on addition of these vegetal extracts were measured. Percentages from the maximal or minimal values obtained were calculated for each extract (TEAC%, PMNL stimulation%, PMNL inhibition%, relative speed of action% (RSA%%)), specific Yin-Yang significance was assigned to each relative parameter. In the end, an integration of all the relative values was done, in order to find a global ”Yin” or a ”Yang” trait of each vegetal extract. Results: TEAC decreased in the following order: SYM > INU > CAL >ANG(F) > ANG(R > ECB. Three vegetal extracts (SYM > INU > ECB) decreased the luminol-enhanced chemiluminescence of PMNL, two (ANG(R) > ANG(F)) increased it, while one (CAL) had a dual effect. After the integration of the percentages, CAL was found to have a global ”Yang” trait, while the rest of the plants had a global ”Yin” trait. Conclusions: TEAC% and PMNL inhibition% appears to correlate with the Yin properties of herbs, while PMNL stimulation% and RSA% might correlate with Yang aspects within the formal TCM classification system, and may be useful criteria in describing the Western herbs from a TCM point of view.